Cocoa and Local Development in the Post-Conflict Era: The Case of the Municipality of Algeciras, Colombia - Ducuara Manrique, Alberto; Andrade Daza, Briyid Marcela (Cooperativismo & Desarrollo, 2025)
This article examines the impact of cocoa farming on the economic and social development of Algeciras, Huila, within the framework of Colombia’s post-conflict context. Following the 2016 peace agreement, cocoa cultivation has emerged as a sustainable and productive alternative for communities affected by violence. Using a qualitative approach, the study explored the experiences of 20 cocoa farmers, focusing on economic sustainability, community resilience, and structural challenges. The findings reveal the economic viability of cocoa, demonstrated by a 35.49% IRR and a positive NPV, as well as its role in fostering social cohesion and sustainable agricultural practices. However, challenges such as limited access to financing, inadequate infrastructure, and climate vulnerability persist. The study highlights the need for comprehensive public policies that strengthen rural infrastructure, participatory governance, and social inclusion to solidify cocoa as a driver of development in post-conflict regions.